Deteriorating Pulmonary Functions in Patients with Rheumatoid Arthritis- A Pilot Study from South India - Shanmugavaradharajan, Vijayabaskaran; Rajesh NT; Divya R; Vasudevan, Damodaran (Current Respiratory Medicine Reviews, 2024)
Background and Objective: Pulmonary involvement is a common extra-articular manifestation of rheumatoid arthritis (RA). The present study attempts to highlight the extent of involvement by assessing lung function using pulmonary function tests (PFTs) in patients with RA. Methods: This pilot study involved 30 patients with RA and an equal number of age- and sexmatched healthy controls. All the study participants were subjected to spirometry and in RA patients, the test was repeated after 30 minutes of administering 400 mcg of salbutamol. PFT values of the controls and the pre and post-values of cases like forced vital capacity (FVC), forced expiratory volume in the first second (FEV1), Percentage of forced expiratory volume in the first second (FEV1%), forced expiratory flow at 25% to 75% of the lung volume (FEF25-75%) and peak expiratory flow rate (PEFR) were recorded. Independent sample t-test or Mann-Whitney U test were used for comparisons. The pre- and post-values of PFT were compared using paired t-test, Welsch's test, or Wilcoxon tests. (p ≤ 0.05 implied statistical significance). Results: PFT variables were significantly lower among patients with RA compared with controls (p<0.05). A significant negative correlation of FEF25%-75% and PEFR with BMI in obese patients (BMI >23) and FVC, FEV1, and PEFR significantly lower in post-menopausal women (p < 0.05) was seen. Conclusion: Based on the pilot study findings, patients in south India with RA could manifest decreased pulmonary functions. Obese patients and post-menopausal females with RA could be at a higher risk, and the administration of nebulized salbutamol could improve pulmonary functions.
Keywords: lungs